Design of a reference control architecture for the energy management of electric vehicles - Marco, James; Vaughan, Nicholas D. (Inderscience, 2012)
The High-Voltage (HV) network within an Electric Vehicle (EV) will typically comprise different energy sources such as fuel cells, batteries and ultracapacitors integrated together through the use of both unidirectional and bidirectional DC-DC converters. Given the multitude of feasible HV network designs, there are obvious advantages in having a unifying control architecture that facilitates the Energy Management (EM) control task. Within this paper, a control Reference Architecture (RA) is proposed that can be employed as a template for the design of the EM control function. Example EM control systems are presented each derived from the same RA, but relating to a different physical configuration of HV network. Simulation results are presented to verify the functional performance of the control systems. In each case, the design trade-offs associated with the functional performance of the EM strategy and the non-functional requirements of modularity and reusability are discussed.
Keywords: EV; electric vehicle; HEV; hybrid electric vehicle; control architecture; EM; energy management; SysML; systems modelling language; systems engineering; object orientation.